Ancient Mediterranean Roots of Perspectives on Human Rights = Les origines antiques méditerranéennes de la dignité de l’homme = Le radici antiche mediterranee della dignità umana - Lefebure, Leo D. (Philosophy & canon law, 2017)
ICESCR and Centesimus Annus are heirs to a long tradition of reflection on justice and the universe. Amid the debates over the theoretical basis for human rights, it is important to recall the value of justice in ancient Mediterranean wisdom traditions that provided the roots for later perspectives. In ancient Egypt, Israel, and Greece, thinkers from a variety of vantage points affirmed a moral order of justice in the universe, which offered a basis for recognizing human dignity and for rebuking human rulers who abused their power. Early Christian reflectionson the identity of the Holy Trinity and Jesus Christ played a decisive role in transforming the understanding of the human person, paving the way for later developments.